Artikel Pemanfaatan Metode Card Sort dalam Upaya Meningkatkan Minat dan Hasil Belajar - Nurlaila Susanti (GHIROH, 2022)
This article is focused on increasing student interest and learning outcomes in the subject of Islamic Religious Education by using the Card Sort method. This research was conducted to determine the extent to which the card sort method can increase student interest and learning outcomes in the subject of Islamic Religious Education. To answer this question, the study in this research used classroom action research. Participants in this study were students of class VII junior high school in Singkep Regency. The results of the data analysis showed that students who took action using the card sort method experienced an increase in their interest and learning outcomes compared to before the action was taken. So that the results of this study can contribute to the world of education in the future, especially Islamic Religious Education.